Web-based e-commerce for Jelita Aimie / Yusrizal Adib Abdul Karim - Abdul Karim, Yusrizal Adib (2023)
This thesis presents the development of an E-commerce system for Jelita Aimie, a fashion retail company. The system, called Jelita Aimie e-commerce system, was created to address the challenges and problems faced by the company’s current business process which are difficult to manage orders for staff, lack of products information for the customers and very time consuming for the customers to purchase products. Three objective was established to achieved the research purposed which are to identify the current business process and problems faced by Jelita Aimie, to design and develop e-commerce website for Jelita Aimie and to evaluate the functionality of the proposed system. The development process was carried out using an adapted waterfall model that consisted of five phases. The methodology was selected due to its simplicity and the systematic approach it offers in developing the system. Through the process of interviewing the operation manager of Jelita Aimie, the current business process and problems with the current business process were identified. In the testing phase, the results that were obtained from expert’s and user’s testing that was done using a test case and questionnaire were hugely positive, where high percentage of the results shows the system developed is easy to use, well function and has great usability. The development of the system and the implementation of the theory into the system development helped to address the problems of the current business processes by achieving all the project objectives. For the future, the system could be improved even more by integrating more and more function that can help the users improve business process.